1999
DOI: 10.1021/jm980622j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Euglycemic and Hypolipidemic Agents. 4. Pyridyl- and Quinolinyl-Containing Thiazolidinediones

Abstract: A series of substituted pyridyl- and quinolinyl-containing 2, 4-thiazolidinediones having interesting cyclic amine as a linker have been synthesized. Both unsaturated thiazolidinediones 5 and saturated thiazolidinediones 6 and their various salts were evaluated in db/db mice for euglycemic and hypolipidemic effects and compared with BRL compound 11 and BRL-49653, respectively. Some of the potent compounds were converted to various salts in order to obtain improved activities. Among all the salts evaluated, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Thus 2-[(y-tdmethylsilylpropyl)thio] derivatives of pyridine 4a and quinoline 6a are more active than the similar derivatives of 4-pyddine 5a and 8-quinoline 7a. (15) '.. The studied compounds have a medium toxicity.…”
Section: Acute Toxicityassaymentioning
confidence: 96%
See 1 more Smart Citation
“…Thus 2-[(y-tdmethylsilylpropyl)thio] derivatives of pyridine 4a and quinoline 6a are more active than the similar derivatives of 4-pyddine 5a and 8-quinoline 7a. (15) '.. The studied compounds have a medium toxicity.…”
Section: Acute Toxicityassaymentioning
confidence: 96%
“…For example, pyridine sulfides display cholesterol acyltransferase inhibitor [1], blood sugar reduction [2], vasodilating [3][4][5][6][7], vasopressing [8], antihypertensive [4,5,7,9,10], hypotensive [6], hypoglycemic [11][12][13], anticholesteremic [14], euglicemic and hypolipidemic [15], cardiotonic [16], cardiovascular and cardioprotective [17] activities. Quinoline sulfides exhibit vasodilating [18][19][20][21][22][23][24], antihypertensive [18,19], hypotensive [23,30], euglicemic and hypolipidemic [15], antithrombotic [31,32] and cardiotonic [32] activities. Thiazole and benzothiazole sulfides display vasodilating [33][34][35], and hypotensive [35] activities and may be used as hypolipemics and in treatment of arteriosclerosis [36].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies of (53) were also reported 68 . Furthermore, the comparative studies between rosiglitazone (4) and PAT5A (53) indicates that, in contrast to rosiglitazone (4), PAT5A (53) inhibits biosynthesis of cholesterol and fatty acid.…”
Section: )mentioning
confidence: 99%
“…▪ The brief review of thiazolidine-2,4-diones were shown that, introduction of several heterocyclic rings are mainly containing nitrogen atom at the lipophilic tail region were identified to have promising glucose lowering activity. These different heterocyclic rings are containing different thiazolidine-2,4-diones such as rosiglitazone (4) 11 , pioglitazone (5) 95 , lobeglitazone (6) 28 , darglitazone (9) 32 , rivoglitazone (11) 36 , mitoglitazone (13) 41,42 , balaglitazone (15) 46 , AD-5061/AD-7057 (20) 20 , DRF-2189 (21) 51 , edaglitazone (25) 56 , PHT46 (28) 58 , PMT13 (29) 13 , DRF-2519 (39) 62 , PAT5A (53) 68 and (54). 70 ▪ Furthermore, in case of different aromatic rings substitutions present at lipophilic tail region of thiazolidine-2,4-diones were shown phenyl ring with H-bond acceptor substitution.…”
mentioning
confidence: 99%
“…PAT-5A showed better glucose and lipid lowering properties than troglitazone and rosiglitazone in different diabetic and dyslipidemic animal models (10)(11)(12). Probe toxicity studies of PAT-5A in Wistar rats showed better tolerance than rosiglitazone (12).…”
Section: Introductionmentioning
confidence: 99%